(untitled) - Primack, Richard (Sunderland, 2002)
Combining theory and basic research, this introductory textbook outlines the connections between conservation biology and fields like environmental economics, ethics, law, and social sciences. The book emphasizes sustainable development and describes the role that the general public, conservation organizations, and governments play in protecting biological diversity.
Keywords: Conservation biology,Bảo tồn sinh học